2001
DOI: 10.1046/j.1475-1313.2001.00583.x
|View full text |Cite
|
Sign up to set email alerts
|

The ChromaGen contact lens system: colour vision test results and subjective responses

Abstract: The ChromaGen lens system is designed to enhance colour perception in colour vision deficiency (CVD). To investigate its efficacy, 14 CVD subjects were prescribed ChromaGen contact lenses. Colour vision tests (Ishihara, Farnsworth Munsell D-15, Farnsworth Lantern) were administered at baseline, lens dispensing, and after a 2-week lens-wearing trial during which subjective responses were recorded daily using visual analogue scales. ChromaGen lenses significantly reduced ishihara error rates (p < 0.001; ANOVA), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 16 publications
1
41
0
1
Order By: Relevance
“…Currently, there is a paucity of primary studies to evaluate the costs and benefits of mass screening for acquired CVD, although some preliminary studies show that doing so may help detect diabetic retinopathy and primary open angle glaucoma earlier [8,58,[59][60][61][62].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there is a paucity of primary studies to evaluate the costs and benefits of mass screening for acquired CVD, although some preliminary studies show that doing so may help detect diabetic retinopathy and primary open angle glaucoma earlier [8,58,[59][60][61][62].…”
Section: Discussionmentioning
confidence: 99%
“…Means of overcoming occupational colour deficiencies used include asking others, using instruments, keeping objects of different colours in separate places and avoiding colour tasks [4]. A 2001 study showed that the use of tinted contact lenses in CVD subjects significantly reduced error rates on the Ishihara and Farnsworth Munsell D-15 test [62]. This may provide some assistance in colour-related Data from Albany-Ward K [16].…”
Section: Discussionmentioning
confidence: 99%
“…64 Interestingly, the most recent small clinical trial of a new lens design found a statistically significant improvement in confusion index scores at the FM-D15 test: this finding cannot easily be explained by the introduction of luminance cues. 65 Any alteration to colour discrimination afforded by monocular tinted lenses is offset by alterations to depth and motion perception. Furthermore, it is clear that such filters do not 'normalise' colour vision.…”
Section: Practical Limitations Of Colour Vision Deficiencymentioning
confidence: 99%
“…Conventional cautions are still needed in its use, however. It would still be possible to cheat on the test perhaps by viewing it with a software application on a smartphone, using a colored filter, 18,19 or simply having another individual supply the answers during the test. Thus, the CCVT does not eliminate oversight by an examiner, although with the CCVT test, the examiner less likely needs to be a color vision specialist or even a health care provider.…”
Section: Discussionmentioning
confidence: 99%